Aplikasi Arsip Surat Mobile Menggunakan Framework Flutter (Studi Kasus: PT. BPD MalukMalut) - Ryan Renaldy Siematauw (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The development of increasingly advanced technology has an impact on all fields of work including banking. In the process of working PT BPDM also has obstacles such as filing letters which are still being done by recording incoming and outgoing letters in a book. Based on the existing problems, it is necessary to design a letter archive application to overcome these problems. This research was built on a mobile basis using the flutter framework and the Dart programming language and using the API as the interface of the application. In designing the system made using the waterfall method where this stage starts from Problem Identification, Literature Study, System Design, System Testing, System Implementation. The results of the research applied to PT BPDM can facilitate the work of employees at PT BPDM in archiving letters and also managing existing letters.